San Miguel Canoa, urban town - Licona Valencia, Ernesto (Benemérita Universidad Autónoma de Puebla, 2019)
This text etnographically examines the Nahua community of San Miguel Canoa (Puebla) a an urban town product of the sociocultural relationship differentiated between an own territory (town) and an external territory (city) that simultaneously integrated by means of mobility and work without abandoning the original language and making social appropriations of the time that make up socioterritorial urban-indigenous expressions in the context of metropolization of the city of Puebla and globalization in general.